Power and transnational activism - edited by Thomas Olesen (Abingdon Routledge, 2011)
This book focuses on global activism and uses a power perspective to provide an in-depth and coherent analysis of both the possibilities and limitations of global activism.
Includes bibliographical references and index.
Keywords: Globalization